Regional Wage Differences in the Netherlands: Micro-Evidence on Agglomeration Externalities - Stefan P.T. Groot; Henri L.F. de Groot; Martijn Smit (Tinbergen Institute, 2011)
Based on micro-data on individual workers for the period 2000-2005, we show that wage differentials in the Netherlands are small but present. A large part of these differentials can be attributed to individual characteristics of workers. Remaining effects are partially explained by variations in employment density, with an elasticity of about 3.8 percent and by Marshall-Arrow-Romer externalities, where doubling the share of a (2-digit NACE) industry results in a 2.4 percent higher productivity. We find evidence for a negative effect of competition (associated with Porter externalities) and diversity (associated with Jacobs externalities).
Keywords: J24; O12; R11; R23; 330; regional labour markets; wage differentials; agglomeration externalities; Regionale Lohnstruktur; Regionaler Arbeitsmarkt; Agglomerationseffekt; Niederlande